Variation in Soil Organic Carbon under Different Forest Types in Shivapuri Nagarjun National Park, Nepal. (3rd November 2021) - Shapkota, Jun; Kafle, Gandhiv
Abstract : Understanding distribution of soil organic carbon (SOC) in soil profile is important for assessing soil fertility and SOC stock because it varies with soils of different vegetation and land use types. In this context, the objective of this research is that it was conducted to determine key variance in the SOC stock in three different soil layers, 0–20 cm, 20–40 cm, and 40–60 cm of different vegetation covers of Shivapuri Nagarjun National Park of Kathmandu district, Nepal. Overall field measurement was based on standard national methods. We used the dichromate digestion method to analyse SOC concentrations. The highest SOC concentration (%) was recorded as 4.87% in 0–20 cm of oak forest and lowest 0.42% in 40–60 cm of Chir pine forest. Forest types (oak, upper mixed hardwood, lower mixed hardwood, and Chir pine) had SOC stock 149.62, 104.47, 62.5, and 50.85 t/ha, respectively, up to 60 cm depth. However, these values are significantly different (p = 0.02 ) at 5% level of significance when comparing means between the forest types. The SOC stock was decreased with increased soil depth, though not significantly different at 5% level of significance. Further study with respect to different climate, soil, forest, and land use type is recommended.